An Exploratory Study On Service Quality Infrastructure In Malaysian Hotels - Qudratullah, Qudratullah; Malik, Ikmal Abd; Razak, Azrin Abdul; Derioh, Grace (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
The purpose of this study is to explore the scope and the level of commitment among employees towards service quality management practises in a hotel's organisation. Descriptive research design is used to know the parameters of service quality management in hotels. By applying a mixed of qualitative and quantitative data collection method from 100 hotels in Kuala Lumpur, 54 hotels responded, resulting in a response rate of 45%. The results indicate that the design and monitoring functions were ranked as the two most important phases in the service management process to incorporate service quality practises into a hotel's infrastructure for improved service quality gap management, followed by the implementation and planning functions.